THE ROLE OF MODERN HR TECHNOLOGIES IN THE EVALUATION AND ANALYSIS OF TEACHERS’ PERFORMANCE IN THE EDUCATION SYSTEM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes the role of modern HR (Human Resources) technologies in the effective evaluation and analysis of teachers’ performance within the education system. It highlights the application of digital management tools, online assessment systems, personal data platforms, and AI-powered analytical systems in the evaluation of teachers’ work. Furthermore, it examines innovative approaches to human resource management in educational institutions and explores the influence of HR technologies on teacher motivation and professional development.